Pengaturan dan Tata Cara Prasarana Pendidikan - Setiyadi, Bradley; Ernawati, Anisa; Kaur, Harsim Bren; Elkanawati, Rahel Agnes; Raudiah, Raudiah; Olviana, Yohana (Universitas Batanghari Jambi, 2024)
This research aims to determine the arrangements and procedures for using educational facilities and infrastructure. This research uses a specific library research approach. Arrangements and procedures for using facilities and infrastructure. This means recording inventory items to track management of facilities and infrastructure, recording non-inventory items, coding incoming goods, and creating a summary list of items. Users of facilities and provide storage space to ensure the quality and quantity of each facility and infrastructure.